2021
DOI: 10.1038/s41598-021-97776-5
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial cell density and morphology in ophthalmologically healthy young individuals in Japan: An observational study of 16842 eyes

Abstract: We aimed to investigate the cell density and morphology of the corneal endothelium in ophthalmologically healthy young Japanese, given the lack of normative data in literature. This observational study included eyes without ophthalmologic diseases, besides refractive errors, examined between 1996 and 2015 at Miyata Eye Hospital. Eyes with a history of ophthalmologic diseases or contact lens usage were excluded. Correlation of corneal endothelial cell density (ECD), coefficient of variation (CV), appearance rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…They found that regardless of age, CD in the posterior layer was inversely and significantly correlated with ECD, CV%, and HEX% [18,26]. The strong and negative correlation between age and ECD, which has already been proven in the literature, could explain the aforementioned results [26][27][28]. Similar to their results, Simsek et al found that the posterior CD in patients with Fuchs uveitis syndrome (FUS), either all concentric annuli or the 0-2 mm zone, was strongly and negatively correlated with ECD (r s = -0.789, p < 0.001 in all concentric annuli; r s = -0.545, p = 0.005 in the 0-2 mm zone) and HEX% (r s = -0.616, p = 0.001 in all concentric annuli; r s = -0.589, p = 0.001 in the 0-2 mm zone) [13].…”
Section: Discussionmentioning
confidence: 72%
“…They found that regardless of age, CD in the posterior layer was inversely and significantly correlated with ECD, CV%, and HEX% [18,26]. The strong and negative correlation between age and ECD, which has already been proven in the literature, could explain the aforementioned results [26][27][28]. Similar to their results, Simsek et al found that the posterior CD in patients with Fuchs uveitis syndrome (FUS), either all concentric annuli or the 0-2 mm zone, was strongly and negatively correlated with ECD (r s = -0.789, p < 0.001 in all concentric annuli; r s = -0.545, p = 0.005 in the 0-2 mm zone) and HEX% (r s = -0.616, p = 0.001 in all concentric annuli; r s = -0.589, p = 0.001 in the 0-2 mm zone) [13].…”
Section: Discussionmentioning
confidence: 72%
“…Figure 1(a) shows a schematic to highlight the range of p 6 values obtained from experiment. The data are subdivided into those obtained as a function of patient age [16][17][18][19][20][21][22][23][24][25][26] , contact lens usage [32][33][34][35] , onset of diabetes [27][28][29][30] , and "other" (here, covering smoking behaviour, non-human species (here, dogs, rabbits and mice) and the behaviour of transplanted tissue 22,31,[57][58][59][60][61] ). A large spread of p 6 values are obtained, ranging from p 6 ∼ 0.36 − 0.88.…”
Section: Trends In P6mentioning
confidence: 99%
“…Experimental data obtained as a function of patient age are shown in figure 2(a). The data are subdivided by the nation of origin of the patient with the published standard deviations shown as error bars [16][17][18][19][20][21][22]25,62,63 . In the majority of cases the fraction of six-membered rings decreases as a function of time (and this is the over-arching trend in all cases).…”
Section: Trends In P6mentioning
confidence: 99%
See 2 more Smart Citations